Arsenic speciation in rice bran: Agronomic practices, postharvest fermentation, and human health risk assessment across the lifespan. (1st December 2021) - Weber, Annika M.; Baxter, Bridget A.; McClung, Anna; Lamb, Molly M.; Becker-Dreps, Sylvia; Vilchez, Samuel; Koita, Ousmane; Wieringa, Frank; Ryan, Elizabeth P.
Abstract: Arsenic (As) exposure is a global public health concern affecting millions worldwide and stems from drinking water and foods containing As. Here, we assessed how agronomic practices and postharvest fermentation techniques influence As concentrations in rice bran, and calculated health risks from consumption. A global suite of 53 rice brans were tested for total As and speciation. Targeted quantification of inorganic As (iAs) concentrations in rice bran were used to calculate Target Hazard Quotient (THQ) and Lifetime Cancer Risk (LCR) across the lifespan. Mean iAs was highest in Thailand rice bran samples (0.619 mg kg −1 ) and lowest in Guatemala (0.017 mg kg −1 ) rice bran samples. When comparing monosodium-methanearsonate (MSMA) treated and the Native-soil counterpart under the irrigation technique Alternate Wetting and Drying (AWD) management, the MSMA treatment had significantly higher total As ( p = 0.022), and iAs ( p = 0.016). No significant differences in As concentrations were found between conventional and organic production, nor between fermented and non-fermented rice bran. Health risk assessment calculations for the highest iAs-rice bran dosage scenario for adults, children and infants exceeded THQ and LCR thresholds, and LCR was above threshold for median iAs-rice bran. This environmental exposure investigation into rice bran provides novel information with food safety guidance for an emerging global ingredient. Graphical abstract: Image 1 Highlights: Rice bran arsenic speciation was quantified across a globally diverse sample set. Agronomic methods such as irrigation influenced arsenic concentrations in rice bran. Postharvest rice bran fermentation minimally impacted arsenic concentrations. Human health risk assessments suggest some rice bran varieties merit dosage regulation.